WEAR AND SERVICE LIFE OF RAILS AND WHEELS OF THE ROLLING STOCK - Karpushenko, M. I.; Kotova, I. O. (Science and Transport Progress, 2003)
The major factors determining the intensity of deterioration of rails and wheels of a rolling stock are determined in the article. The measurements of lateral rails deterioration in curve sites of a way, the factors influencing intensity of deterioration are revealed as a result of the analysis.